2021
DOI: 10.2147/ppa.s269119
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Adherence to Treatment and Quality of Life for a Group of Patients with Essential Hypertension in Romania

Abstract: Purpose Romania has a high prevalence of hypertension (45.1% in 2016). Whether this is attributable to a low rate of treatment adherence—which can aggravate the pathology and reduce patients’ quality of life (QoL)—is unknown. To address this point, the present study investigated the factors that influence short- and long-term adherence and QoL in patients with arterial hypertension using a specially designed questionnaire. Patients and Methods The study enrolled 289 pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…17 18 A recent survey reported that patients with hypertension’s social activity was significantly affected by the symptoms or medication side effects and suggested that symptoms and concern about complications can have unfavourable influence on not only the mental, but also the social domain of quality of life. 19 However, it was uncertain what kind of social activity was affected in this study because the information of questionnaire was not adequately provided. Further qualitative study is warranted to specify the social dimension of patients’ illness experiences.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…17 18 A recent survey reported that patients with hypertension’s social activity was significantly affected by the symptoms or medication side effects and suggested that symptoms and concern about complications can have unfavourable influence on not only the mental, but also the social domain of quality of life. 19 However, it was uncertain what kind of social activity was affected in this study because the information of questionnaire was not adequately provided. Further qualitative study is warranted to specify the social dimension of patients’ illness experiences.…”
Section: Introductionmentioning
confidence: 90%
“…Though hypertension has never been viewed as a disease associated with stigmatisation, it remains to be seen considering that patients cannot be assumed to be free of suffering just because their diseases are asymptomatic and controllable, as in the case with HIV disease 17 18. A recent survey reported that patients with hypertension’s social activity was significantly affected by the symptoms or medication side effects and suggested that symptoms and concern about complications can have unfavourable influence on not only the mental, but also the social domain of quality of life 19. However, it was uncertain what kind of social activity was affected in this study because the information of questionnaire was not adequately provided.…”
Section: Introductionmentioning
confidence: 99%
“…Adherence to treatment, which is the extent to which a person performs behaviors such as taking medication, following a diet, or implementing changes in lifestyle according to the recommendations provided by healthcare personnel [16], is a complex behavioral process that is in uenced by many factors such as the patient's psychological state, social support, healthcare system, and individual and psychological characteristics. It is also affected by other factors such as the type of disease, lifestyle, demographics, self-e cacy, informational motivation, insu cient knowledge about the disease and unfavorable relations with the treatment staff, negative drug attitude, and worry [17][18][19][20], as some studies have reported that chronic patients adhere to treatment regimens by 20-60% [9].…”
Section: Introductionmentioning
confidence: 99%